English Language Learning Through The Use of Digital Technology: A Literature Review - Cyntia Lady Indriani; Abdul Muth’im; Emma Rosana Febriyanti (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research aims to evaluate the impact of digital technology on English language learning by synthesizing findings from various studies to understand its role in enhancing language skills. This review explores the potential of digital resources such as games, mobile applications, and online platforms in improving writing skills, particularly in higher education contexts. The research method is inspired by socio-cultural, cognitive, and constructivist theories, focusing on the complex interaction between technology and language acquisition, with notable achievements in pronunciation training and chat platforms. The research findings indicate that this review supports cautious optimism, encouraging educators to integrate technology wisely in line with pedagogical principles. The conclusion is a balanced approach that leverages the strengths of technology to create more meaningful and effective English language learning experiences for all learners. Keywords: Digital Literacy; Digital Technology; English Language Learning; Language Acquisition; Pedagogical Integration